ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETIMPANGAN PENDAPATAN DI PULAU SUMATERA TAHUN 2015 - 2024 - Gabriel Amadeus Sitompul; M. Syafii; Arif Rahman (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the factors affecting income inequality in Sumatra in the short and long term for the period 2015-2024. The variables studied include HDI, TPT, inflation, PMDN, PMA, and economic growth as independent variables. Income inequality is used as the dependent variable. The research data consists of panel data comprising cross-sectional data from 10 provinces on the island of Sumatra and time-series data for the period 2015–2024. Since the cointegration test revealed a cointegration relationship among the variables, the research model employed is the Panel Vector Error Correction Model (Panel VECM). This study was conducted using the E-Views data analysis software. Research findings on income inequality on the island of Sumatra indicate that in the short term, the Human Development Index (HDI) has a positive and significant effect, the Unemployment Rate (UR) has a negative and significant effect, inflation has a positive but insignificant effect, Domestic Investment (PMDN) has a negative but insignificant effect, Foreign Direct Investment (PMA) has a negative but insignificant effect, and economic growth has a positive but insignificant effect. In the long term, the HDI has a negative but insignificant effect; the TPT has a positive but insignificant effect; inflation has a positive and significant effect; domestic investment (PMDN) has a negative and significant effect; foreign investment (PMA) has a positive and significant effect; and economic growth has a negative and significant effect.